The impact of 100 hours of exercise and sleep deprivation on cognitive function and physical capacities - Lucas, S. J. E.; Anson, J. G.; Palmer, C. D.; Hellemans, I. J.; Cotter, J. D. (Journal of Sports Sciences, 2009)
In this study, we examined the effect of 96-125 h of competitive exercise on cognitive and physical performance. Cognitive performance was assessed using the Stroop test (n = 9) before, during, and after the 2003 Southern Traverse adventure race. Strength (MVC) and strength endurance (time to failure at 70% current MVC) of the knee extensor and elbow flexor muscles were assessed before and after racing. Changes in vertical jump (n = 24) and 30-s Wingate performance (n = 27) were assessed in a different group of athletes. Complex response times were affected by the race (16% slower), although not significantly so (P = 0.18), and were dependent on exercise intensity (less so at 50% peak power output after racing). Reduction of strength (P < 0.05) of the legs (17%) and arms (11%) was equivalent (P = 0.17). Reductions in strength endurance were inconsistent (legs 18%, P = 0.09; arms 13%, P = 0.40), but were equivalent between limbs (P = 0.80). Similar reductions were observed in jump height (-8 ± 9%, P < 0.01) and Wingate peak power (-7 ± 15%, P = 0.04), mean power (-7 ± 11%, P < 0.01), and end power (-10 ± 11%, P < 0.01). We concluded that: moderate-intensity exercise may help complex decision making during sustained stress; functional performance was modestly impacted, and the upper and lower limbs were affected similarly despite being used disproportionately.